A Preliminary Survey of Mycotoxins Identified from Florida Bahiagrass Pastures - Hui-Ling Liao; Ko-Hsuan Chen; Florencia Marcon; Robert (Robbie) Jones; Brittany Justesen; Joseph Walter; Ann Blount; Cheryl Mackowiak; Doug Mayo; Marcelo Wallau (EDIS)
The beef cattle ranchers in Florida reported some health issues related to cattle grazing on warm-season grass pastures, such as bahiagrass and bermudagrass. The illness was not attributable to nutritional imbalances, or other possible causes. The focus then turned to what the animals were consuming, and forages were implicated. In general, the forages in Florida are just fine; however, sometimes under certain circumstances the fungi live in our forages may produce “secondary metabolites”. All forages harbor fungi. Some fungi are good in that they aid our forages to grow better, helping to mine nutrients from the soil or atmosphere. Sometimes they are not so good, like when high levels of ergotized seed occur in the seed heads of bahiagrass.